1974
DOI: 10.1007/bf01221979
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chinese hamsters by metabolic balance, glucose tolerance and insulin secretion

Abstract: Lack of obesity in the hyperphagic Chinese hamster is due to a normal calorie retention. This is related to a greater loss of carbohydrate calories via urine and feces in hyperphagic animals and a reduced absorption of dietary fat. --Various types of glueosurie animals were not adequately characterized by food consumption, blood sugar, quantitated glueosuria and blood sugar or plasma insulin levels after a glucose load. Plasma insulin as well as blood sugar levels appeared to be influenced by stress. Overnight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…HoweiTer, in another experiment, the same low-fat diet was fed ad lib. to similar ketonuric hamsters for 17 d. It was observed that P-cell granulation improved (Gerritsen & Blanks, 1975). The possibility existed that feeding the low-fat diet with lower energy density resulted in less demand for insulin and less ketogenesis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…HoweiTer, in another experiment, the same low-fat diet was fed ad lib. to similar ketonuric hamsters for 17 d. It was observed that P-cell granulation improved (Gerritsen & Blanks, 1975). The possibility existed that feeding the low-fat diet with lower energy density resulted in less demand for insulin and less ketogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…There is little doubt that diabetes mellitus is influenced by factors such as life style (Medalie et al 1978;West, 1978), uterine environment (Gerritsen, 1975 West, 1978). However, there is little agreement about the importance of specific dietary components.…”
mentioning
confidence: 99%
“…25 The genetically diabetic Chinese hamster is glucose-intolerant and the degree of intolerance is related to severity of the disease. 29 Onset of glycosuria varies from 2 wk to 4 mo of age (Table 1).…”
Section: Physiological Characteristicsmentioning
confidence: 99%
“…33 It is of some interest that ad libitum food consumption varies with the severity of the disease but metabolic balance studies show that calories retained are similar (15 K cal/day) regardless of caloric intake. 29 The more severe the diabetes, the more animals eat but, conversely, the more calories lost via urine and feces.…”
Section: Nutrition and Environmentmentioning
confidence: 99%
“…Diabetes in this model is hereditary and characterized by hyperphagia, polydispsia, glycosuria, hyperglycemia and decreased longevity (Sims & Landau, 1967;Gerritsen & Dulin, 1967;Gerritsen & Blanks, 1974). The hamsters are not obese.…”
mentioning
confidence: 99%